Literasi Financial Technology dan Pengenalan Aplikasi Flip.id untuk Meningkatkan Pemberdayaan Warga Pelaku Usaha di Kecamatan Pondok Aren - Puspitarini, Sari; Sari, Rachi Titi Ramadhani (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2024)
Financial technology, or FinTech, is an innovation in technology designed to facilitate financial transactions so that they can be carried out practically, easily, and efficiently using computer devices or mobile phones via the internet. Thanks to the wide range of services offered by FinTech, people can enjoy better financial services and speed up business processes by increasing the speed of money circulation, which in turn can boost the communal economy. For example, the recently launched FLIP app makes it easy to transfer between banks without fees, reducing expenses. In Pondok Aren District, South Tangerang, the use of internet networks by business actors is quite common. However, business residents in Pondok Aren sub-district are often limited in understanding finance in today's digital era and lack of use of technology in financial activities. For this reason, we are encouraged to disseminate knowledge through educational programs to the public and business actors about FinTech literacy  and the introduction of Flip.id applications, in order to increase the empowerment of business residents in Pondok Aren, Tangsel, in order to develop their business optimally.